Influence of different hand positions on impact forces and elbow loading during the round off in gymnastics: a case study - Farana, R.; Jandacka, D.; Irwin, G. (Science of Gymnastics Journal, 2013)
The round-off is a fundamental gymnastics skill and a key movement in the development of elite female gymnasts. The aim of this study was to determine whether differences in hand position during the round-off may influence the ground reaction forces and elbow joint moments in female artistic gymnastics. One international level active female gymnast from the Czech Republic participated in this study. Two force plates were used to determine ground reaction forces. A motion-capture system consisting of eight infrared cameras were employed to collect the kinematic data. The gymnast performed 10 trials of a round-off from a hurdle step to back handspring with a "parallel" hand position and 10 trials with a "T" shape hand position. Effect size statistics were used to establish differences in means. In conclusion "T" position of the second hand reduces vertical and anterior-posterior ground reaction forces. Differences in joint elbow moments and elbow kinematics indicated that the "T" position may prevent elbow joint complex and reduces potential of elbow injuries.